The Influence of Principal’s Leadership Style and Organizational Culture on Teacher’s Performance - Maryati, Eni; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2020)
The objectives of this study were to determine the influence of the principal's leadership style and organizational culture on teacher performance. This research used quantitative method with post-facto research type. The population of the study was 180 elementary school teachers with the status of State Civil Servants or Aparatur Sipil Negara in Sembawa Sub-district, Banyuasin Regency. The sample of research was 108 people. The sampling technique in this study used a table to determine the number of samples developed by Isaac and Michael. Data collection techniques used a questionnaire. Data were analyzed using correlation analysis and multiple regression techniques. The results of this study showed that: (1) the principal's leadership style influences teacher performance by 50.7%; (2) organizational culture influences teacher performance by 48.2%; and (3) the principal's leadership style and organizational culture simultaneously have a positive effect on teacher performance at 59.5% and others were influenced by other variables outside the study. It is recommended that elementary school teachers improve their performance through awareness in carrying out their duties and responsibilities.